Development of vaccines toward the global control and eradication of foot-and-mouth disease. (March 2011) - Rodriguez, Luis L; Gay, Cyril G
Foot-and-mouth disease (FMD) is one of the most economically and socially devastating diseases affecting animal agriculture throughout the world. Although mortality is usually low in adult animals, millions of animals have been killed in efforts to rapidly control and eradicate FMD. The causing virus, FMD virus (FMDV), is a highly variable RNA virus occurring in seven serotypes (A, O, C, Asia 1, Sat 1, Sat 2 and Sat 3) and a large number of subtypes. FMDV is one of the most infectious agents known, affecting cloven-hoofed animals with significant variations in infectivity and virus transmission. Although inactivated FMD vaccines have been available for decades, there is little or no cross-protection across serotypes and subtypes, requiring vaccines that are matched to circulating field strains. Current inactivated vaccines require growth of virulent virus, posing a threat of escape from manufacturing sites, have limited shelf life and require re-vaccination every 4––12 months. These vaccines have aided in the eradication of FMD from Europe and the control of clinical disease in many parts of the world, albeit at a very high cost. However, FMDV persists in endemic regions impacting millions of people dependent on livestock for food and their livelihood. Usually associated with developing countries that lack the resources to control it, FMD is a global problem and the World Organization for Animal Health and the United Nations'' Food Agriculture Organization have called for its global control and eradication. One of the main limitations to FMDV eradication is the lack of vaccines designed for this purpose, vaccines that not only protect against clinical signs but that can actually prevent infection and effectively interrupt the natural transmission cycle. These vaccines should be safely and inexpensively produced, be easy to deliver, and also be capable of inducing lifelong immunity against multiple serotypes and subtypes. Furthermore, there is a need for better integrated strategies that fit the specific needs of endemic regions. Availability of these critical components will greatly enhance the chances for the global control and eradication of FMDV.